Wind power plant as a city skyline and city energy center: The case of Çatalca - Alçiçek, Adem Bağış (Springer Science and Business Media Deutschland GmbH, 2023)
The energy demand in cities around the world increases as residential areas and industrial areas increase. Today, the quality of energy is important in the energy production phase in response to the energy demand. Energy production methods are becoming more and more preferred, with the least harm to the environment. Compared to its wind energy counterparts, it stands as a more environmentally friendly type of energy. Wind power plants are used for wind energy production and these structures are increasing on a global scale. In line with the global trend, Türkiye also gets its share from it. The largest district of the country’s economically largest province in terms of surface area is quite prone to the installation of the aforementioned wind power plants in terms of various features. Carrying the importance it had in the past in terms of defense strategy, water resources and agriculture in terms of energy production, Çatalca is gaining a new urban silhouette with the increase in wind power plants. It is also evolving into a city energy centre. These developments seem to herald a rapid urban transformation for Çatalca.
Keywords: City Skyline; Energy; Wind Power Plant; Çatalca